2016
DOI: 10.1590/2237-6089-2016-0012
|View full text |Cite
|
Sign up to set email alerts
|

Semantic validation of the ISPCAN Child Abuse Screening Tools (ICAST) in Brazilian Portuguese

Abstract: Objective: The International Society for the Prevention of Child Abuse and Neglect (ISPCAN) Child Abuse Screening Tools (ICAST) is a battery of questionnaires created by the World Health Organization, the United Nations and ISPCAN for researching maltreatment in childhood. This study aims to translate, to adapt and to validate the semantic equivalence of all items on the three questionnaires: ICAST-C (ICAST version for Children), ICAST-R (Retrospective Interview) and ICAST-P (ICAST version for Parents). Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…A study of the Brazilian-Portugese adaptation of ICAST-C noted that 7 of 59 variables were not valid and had to be changed or eliminated. 15 A previous study showed reliable alpha values for three ICAST instrument ranging from 0.69 to 0.89. 11 However, in our study the total alpha value was 0.919, which was considered to be very good reliability, despite the unreliable alpha values for domains of violence exposure and neglect (0.483 and 0.445, respectively).…”
Section: Discussionmentioning
confidence: 92%
“…A study of the Brazilian-Portugese adaptation of ICAST-C noted that 7 of 59 variables were not valid and had to be changed or eliminated. 15 A previous study showed reliable alpha values for three ICAST instrument ranging from 0.69 to 0.89. 11 However, in our study the total alpha value was 0.919, which was considered to be very good reliability, despite the unreliable alpha values for domains of violence exposure and neglect (0.483 and 0.445, respectively).…”
Section: Discussionmentioning
confidence: 92%
“…Table 4 illustrates the final number of deleted items in the ICAST-CH-M with satisfactory Cronbach’s alpha in each domain compared to the original English ICAST-CH ( 17 ).…”
Section: Resultsmentioning
confidence: 99%
“… Notes: * I = physical and psychological abuse; II = neglect; III = sexual abuse; IV = exposure to domestic violence; V = exposure to community violence; # ( 17 ) …”
Section: Figurementioning
confidence: 99%
“…Childhood abuse has been found to be a powerful predictor both at social and environmental level that can be a leading risk factor of death and disability at any stage of life (Silveira & Grassi-Oliveira, 2016). In a recent research compilation neglect and childhood abuse are reported to be more common in countries that are struggling with cultural influences, development and economical issues.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent research compilation neglect and childhood abuse are reported to be more common in countries that are struggling with cultural influences, development and economical issues. (Silveira & Grassi-Oliveira, 2016). Child abuse is under reported and under recorded in history.…”
Section: Introductionmentioning
confidence: 99%